Analysis of the Level of Traffic Fatality of Road Section Conditions in Tanjung Balai City - Sihombing, Alexander Tuahta; Pratikso, Pratikso; Mudiyono, Rachmat (ASTONJADRO, 2025)
There are various kinds of driver behavior in Tanjungbalai city such as aggressive driving, illegal racing, against the direction and many more which are generally dominated by workers with different professions and students. A person’s attitude and pattern of thinking will be influenced by that pattern of thinking, which usually results in certain patterns of behavior. Most traffic accidents occur due to human error, such as traffic violations. Every year, 1.35 million people die from traffic accidents worldwide. This means that every 24 seconds one person loses their life on the roads around the world. A person can violate traffic laws due to intentionality, ignorance, or ignorance of the applicable rules. This study explains, which means testing hypotheses to explain the causal relationship between variables. This type of research was chosen because the goal to be achieved was to explain the relationship and effect of the questionnaire as the main data collection tool. Field research requires tools to support it. The following tools and materials were used by researchers including stationery, cameras (documentation) and survey forms Traffic Accident Analysis. Data Collection Techniques The research data must be collected to obtain the necessary data and information. The following is the data collection process used in this study, namely Primary Data Survey Results where primary data collection is carried out by direct observation at the research location. Secondary Data where vehicle data and vehicle volumes used as writing material are based on direct observation data in the field and data assistance from SAMSAT and the PUPR Office of Tanjungbalai City. Field Observation is by making direct observations of motorists who are around the research subject to collect information needed for further research. As well as documentation Data collected from activities carried out at the research location or survey during the activity. This research was conducted in Tanjung Balai City, North Sumatra Province with research targets or respondents being Students, Students, and Communities who live or are in the research area and own and use motorized vehicles (cars and motorcycles) spread across Gading Village, Sijambi Village, and Pahang Village, Tanjung Balai City.Research Implementation Time Where the research took place for four days, from March 11 to 14, 2024. The research location is located at Ir. Sutami street, Husni Thamrin street, Abd Rahman Street, and SMA 3 street, Tanjung Balai City. It can be seen that the most frequent traffic accidents in the research location are on the Ir. Sutami section of Tanjungbalai City which has an accident rate which if rounded off the value is 36 events/year. From the calculation example above, it is known that the value of the fatality rate of the Ir Sutami road section, Datuk Bandar District, Tanjungbalai with TF = 47232.003> UCL = 23903.06 then the road section is an Accident Prone Area. The accident-prone road section that has the highest fatality rate is Jl. SMA 3, Tanjungbalai with TF = 105462,206 and UCL = 61843,521.